Evaluating programmatic reactive focal drug administration impact on malaria incidence in northern Senegal: an interrupted time series analysis - Ellen Leah Ferriss; Yakou Dieye; Moustapha Cissé; Gnagna Dieng Sow; Jean Louis Lankia; Damien Diedhiou; Abiboulaye Sall; Tamba Souane; Tidiane Thiam; Doudou Sene; Elhadji Doucouré; Ibrahima Diallo; et al. (Malaria Journal)
Abstract Background The World Health Organization conditionally recommends reactive drug administration to reduce malaria transmission in settings approaching elimination. However, few studies have evaluated the impact of reactive focal drug administration (rFDA) in sub-Saharan Africa, and none have evaluated it under programmatic conditions. In 2016, Senegal’s national malaria control programme introduced rFDA, the presumptive treatment of compound members of a person with confirmed malaria, and reactive mass focal drug administration (rMFDA), an expanded effort including neighbouring compounds during an outbreak, in 10 low transmission districts in the north of the country. This evaluation sought to measure the impact of rFDA and rMFDA on malaria incidence. Methods An interrupted time series analysis was conducted with routine surveillance data on health post-level monthly confirmed malaria case counts from the District Health Information Software (DHIS2). The study evaluated the change in incidence following rFDA and rMFDA rollout (level change), which ranged from August 2016 to November 2019, and monthly thereafter (trend change), using an adjusted negative binomial regression model with data from January 2015 through January 2020. The model was used to estimate the number of cases averted via a counterfactual simulation. Results No incidence rate reductions were estimated immediately following rollout (level change: incidence rate ratio (IRR) = 1.00, 95% credible interval (CI) = 0.76, 1.33). However, rFDA and rMFDA were associated with a 4% monthly decline in incidence relative to the baseline trend (trend change: IRR = 0.96, 95% CI = 0.95, 0.98). Over the study period, RFDA and rMFDA were estimated to avert 2,070 (95% CI = 577, 4,367) of 4,108 (95% CI = 2,620, 6,425) malaria cases. Conclusions RFDA and rMFDA were associated with reduced malaria incidence in northern Senegal, supporting their use in malaria control in very low transmission areas. However, additional strategies are likely needed to achieve elimination in this setting.